Skip to main content

Eventual periodicity of the fuzzy max-difference equation \(x_{n} = \max \{ C, \frac{x_{n-m-k}}{x_{n-m}}\}\)

Abstract

In this paper, we study the eventual periodicity of the fuzzy max-type difference equation \(x_{n} =\max \{C , \frac{x_{n-m-k}}{x_{n-m} }\}, n\in \{0,1,\ldots \} \), where m and k are positive integers, C and the initial values are positive fuzzy numbers. Let the support \(\operatorname{supp} C=\overline{\{t : C(t) > 0\}}=[C_{1},C_{2}]\) of C. We show that: (1) if \(C_{1}>1\), then every positive solution of this equation equals C eventually; (2) there exists a positive fuzzy number C with \(C_{1}=1\) such that this equation has a positive solution which is not eventually periodic; (3) if \(C_{2}\leq 1\), then this equation has a positive solution which is not eventually periodic; (4) if \(C_{1}<1<C_{2}\), then every positive solution of the above equation is not eventually periodic.

Introduction

It is well known that difference equations and difference equation systems are often used in the study of linear and nonlinear physical, physiological, and economical problems (for instance, see [1, 2]). In the recent years, because the max operator has a great importance in automatic control models (see [3, 4]), max-type difference equations and systems which are a special type of difference equations and difference equation systems have attracted the attention of many scholars (for instance, see [515]).

In [16], Mishev et al. proved that every solution of the difference equation

$$ x_{n+1}=\max \biggl\{ A,\frac{x_{n}}{x_{n-1}}\biggr\} ,\quad n\in { \mathbf{N}}_{0}\equiv \{0,1,\ldots \}, $$

is eventually periodic, where \(A\in {\mathbf{R}}_{+}\equiv (0,+\infty )\).

In [17], Fotiades and Papaschinopoulos studied the following max-type system of difference equations:

$$ \textstyle\begin{cases} x_{n} = \max \{A ,\frac{y_{n-1}}{x_{n-2}} \}, \\ y_{n} = \max \{B ,\frac{x_{n-1}}{y_{n-2}} \},\end{cases}\displaystyle n\in {\mathbf{{N}}}_{0}, $$

with \(A,B\in {\mathbf{R}}_{+}\) and showed that every positive solution of the above system is eventually periodic.

Further, Su et al. [18] studied eventual periodicity of the following max-type system of difference equations:

$$ \textstyle\begin{cases} x_{n} = \max \{A_{n} ,\frac{y_{n-1}}{x_{n-2}} \}, \\ y_{n} = \max \{B_{n} ,\frac{x_{n-1}}{y_{n-2}} \},\end{cases}\displaystyle n\in {\mathbf{{N}}}_{0}, $$

where \(A_{n},B_{n}\in {\mathbf{R}}_{+}\) are periodic sequences with period 2 and the initial values \(x_{-2},y_{-2}, x_{-1}, y_{-1}\in {\mathbf{R}}_{+}\) and showed that every solution of the above system is eventually periodic.

Recently there has been a growing interest in the study of fuzzy difference equations (for instance, see [1931]) because many models in biology, ecology, physiology physics, engineering, economics, probability theory, genetics, psychology and resource management are represented by these equations naturally. For example, fuzzy difference equations are suitable in finance problems. Chrysafis et al. [32] studied the fuzzy difference equation of finance. Their research is in finance which is about the alternative methodology to study the time value of money. In [33], Deeba and Korvin studied the second-order linear difference equation

$$ x_{n+1} = x_{n}-ABx_{n-1}+C, \quad n\in { \mathbf{N}}_{0}, $$

where \(A,B,C\) and the initial values \(x_{0},x_{-1}\) are fuzzy numbers. This fuzzy equation is a linearized model of a nonlinear model which determines the carbon dioxide \((CO_{2})\) level in the blood.

In [34], Rahmana et al. studied the qualitative behavior of the following second-order fuzzy rational difference equation:

$$ x_{n+1} = \frac{x_{n-1}}{A+Bx_{n-1}x_{n}},\quad n\in {\mathbf{N}}_{0}, $$

where \(A,B\) and the initial values \(x_{0},x_{-1}\) are positive fuzzy numbers.

In [35], Stefanidou and Papaschinopoulos studied the periodicity of the following fuzzy max-difference equation:

$$ z_{n+1}=\max \biggl\{ \frac{A}{z_{n}},\frac{A}{z_{n-1}},\ldots , \frac{A}{z_{n-k}}\biggr\} ,\quad n\in {\mathbf{N}}_{0}, $$

and

$$ z_{n+1}=\max \biggl\{ \frac{A}{z_{n}},\frac{B}{z_{n-1}}\biggr\} ,\quad n \in {\mathbf{N}}_{0}, $$

where \(k\in {\mathbf{N}}\equiv \{1,2,\ldots \}\), \(A,B\) and the initial values \(z_{i}\ (i\in {\mathbf{Z}}(-k,0))\) are positive fuzzy numbers (where \({\mathbf{Z}}(a,b)\equiv \{a,\ldots ,b\}\) for any integers \(a,b\) with \(a\leq b\)).

Furthermore, Stefanidou and Papaschinopoulos [36] studied the periodicity of the following fuzzy max-difference equation:

$$ z_{n}=\max \biggl\{ \frac{A}{z_{n-k}},\frac{B}{z_{n-m}}\biggr\} ,\quad n\in {\mathbf{N}}_{0}, $$

where \(A,B\) and the initial values \(z_{i}\ (i\in {\mathbf{Z}}(-d,0))\) with \(d=\max \{k,m\}\) are positive fuzzy numbers. In [37], the authors investigated the periodicity of the positive solutions of the fuzzy max-difference equation

$$ x_{n}=\max \biggl\{ \frac{1}{x_{n-m}},\frac{\alpha _{n}}{x_{n-r}}\biggr\} ,\quad n \in {\mathbf{N}}_{0}, $$

where \(k,m\in {\mathbf{N}}\), \(\alpha _{n}\) is a periodic sequence of positive fuzzy numbers and \(x_{i}\ (i\in {\mathbf{Z}}(-d,0))\) with \(d=\max \{r,m\}\) are positive fuzzy numbers, and showed that, if \(\max (\operatorname{supp} \alpha _{n}) < 1\), then every positive fuzzy number solution of the above equation is eventually periodic with period 2m.

Motivated by the above-mentioned studies for ordinary difference equations and corresponding fuzzy difference equations, this paper is to study the eventual periodicity of the following fuzzy max-difference equation:

$$ x_{n} =\max \biggl\{ C , \frac{x_{n-m-k} }{x_{n-m} }\biggr\} ,\quad n\in { \mathbf{N}}_{0}, $$
(1.1)

where \(m,k\in {\mathbf{N}}\), C and the initial values \(x_{i}\ (i\in {\mathbf{Z}}(-m-k,-1))\) are positive fuzzy numbers.

The rest of this paper is organized as follows. We give some definitions and notations in Sect. 2 and give the main results and their proofs of this paper in Sect. 3.

Preliminaries and definitions

For the convenience of the reader, we give the following definitions and notations.

  1. (1)

    If A is a function from \({\mathbf{R}}=(-\infty ,+\infty )\) into the interval \([0, 1]\), then A is called a fuzzy set.

  2. (2)

    A fuzzy set A is said to be fuzzy convex if \(A(\lambda t_{1}+(1-\lambda )t_{2})\geq \min \{A(t_{1}),A(t_{2})\}\) for any \(\lambda \in [0,1]\) and any \(t_{1},t_{2}\in {\mathbf{R}}\).

  3. (3)

    A fuzzy set A is said to be normal if there exists some \(t\in {\mathbf{R}}\) such that \(A(t)=1\).

  4. (4)

    If A is a fuzzy set, then by a λ-cut of A (for any \(\lambda \in [0,1]\)) we mean the set \(A_{\lambda }= \{t\in {\mathbf{R}}: A(t)\geq \lambda \}\).

It is well known that the λ-cuts of A determine the fuzzy set A. For a subset set B of R we denote by the closure of B.

Definition 2.1

(see [38])

We say that a fuzzy set A is a fuzzy number if it satisfies the following conditions (i)–(iv):

  1. (i)

    A is normal;

  2. (ii)

    A is fuzzy convex;

  3. (iii)

    A is upper semicontinuous;

  4. (iv)

    The support of A, \(\operatorname{supp} A=\overline{\bigcup_{\lambda \in (0,1]}A_{\lambda }}= \overline{\{t : A(t) > 0\}}\) is compact.

It is clear that \(A_{\lambda }\) is a closed interval. A fuzzy number A is said to be positive if \(\min (\operatorname{supp} A)>0\). Denote by \(\mathcal{F}^{+}\) the set of all positive fuzzy numbers. If \(B\in {\mathbf{R}}\), then B is a fuzzy number with \(B_{\lambda }= [B,B]\) for any \(\lambda \in [0,1]\), which is said to be a trivial fuzzy number. By [38] we see that, for any \(\lambda \in (0,1]\),

$$ [x_{n}]_{\lambda }=\max \biggl\{ [C]_{\lambda }, \frac{[x_{n-m-k}]_{\lambda }}{[x_{n-m}]_{\lambda }}\biggr\} . $$
(2.1)

Proposition 2.1

In (2.1), let \([x_{i}]_{\lambda }=[y_{i,\lambda },z_{i,\lambda }]\ (i\in \{n,n-m,n-m-k \})\) and \([C]_{\lambda }=[C_{l,\lambda },C_{r,\lambda }]\) for any \(\lambda \in (0,1]\). Then

$$ \textstyle\begin{cases} y_{n,\lambda }=\max \{C_{l,\lambda } , \frac{y_{n-m-k,\lambda } }{z_{n-m,\lambda }}\}, \\ z_{n,\lambda }=\max \{C_{r,\lambda } , \frac{z_{n-m-k,\lambda }}{y_{n-m,\lambda }}\}.\end{cases} $$
(2.2)

Proof

It follows from (2.1) that, for any \(\lambda \in (0,1]\), we have

$$ [y_{n,\lambda },z_{n,\lambda }]=\max \biggl\{ [C_{l,\lambda },C_{r,\lambda }], \frac{[y_{n-m-k,\lambda },z_{n-m-k,\lambda }]}{[y_{n-m,\lambda },z_{n-m,\lambda }]} \biggr\} . $$

Let \(a_{\lambda },a'_{\lambda }\in [y_{n-m-k,\lambda },z_{n-m-k,\lambda }] ,b_{\lambda },b'_{\lambda }\in [y_{n-m,\lambda },z_{n-m,\lambda }], c_{\lambda },c'_{\lambda }\in [C_{l,\lambda },C_{r,\lambda }]\) such that

$$ y_{n,\lambda }=\max \biggl\{ c_{\lambda },\frac{a_{\lambda }}{b_{\lambda }}\biggr\} ,\qquad z_{n,\lambda }=\max \biggl\{ c'_{\lambda },\frac{a'_{\lambda }}{b'_{\lambda }} \biggr\} . $$

Then we obtain

$$\begin{aligned} &y_{n,\lambda }=\max \biggl\{ c_{\lambda },\frac{a_{\lambda }}{b_{\lambda }}\biggr\} \geq \max \biggl\{ C_{l,\lambda } , \frac{y_{n-m-k,\lambda } }{z_{n-m,\lambda }}\biggr\} \geq y_{n,\lambda }, \\ &z_{n,\lambda }=\max \biggl\{ c'_{\lambda }, \frac{a'_{\lambda }}{b'_{\lambda }}\biggr\} \leq \max \biggl\{ C_{r,\lambda } , \frac{z_{n-m-k,\lambda } }{y_{n-m,\lambda }} \biggr\} \leq z_{n,\lambda }, \end{aligned}$$

from which it follows that

$$ \textstyle\begin{cases} y_{n,\lambda }=\max \{C_{l,\lambda } , \frac{y_{n-m-k,\lambda } }{z_{n-m,\lambda }}\}, \\ z_{n,\lambda }=\max \{C_{r,\lambda } , \frac{z_{n-m-k,\lambda }}{y_{n-m,\lambda }}\}.\end{cases} $$

Proposition 2.1 is proven. □

Definition 2.2

A sequence of positive fuzzy numbers \(\{x_{n}\}_{n=-m-k}^{\infty }\) is said to be a positive solution of Eq. (1.1) if it satisfies (1.1). \(\{x_{n}\}_{n=-m-k}^{\infty }\) is said to be eventually periodic with period T if there exists \(M\in {\mathbf{N}}\) such that \(x_{n+T} = x_{n} \) for all \(n\geq M\).

Proposition 2.2

Let \(x_{i}\in {\mathcal{F}}^{+}\ (i\in {\mathbf{Z}}(-m-k,-1))\). Then there exists a unique positive solution \(\{x_{n}\}_{n=-m-k}^{\infty }\) of (1.1) with initial values \(x_{i}\ (i\in {\mathbf{Z}}(-m-k,-1))\).

Proof

The proof is similar to that of Proposition 3.1 of [39]. For any \(\lambda \in (0,1]\), write

$$ C_{\lambda }=[C_{l,\lambda },C_{r,\lambda }] \quad\text{and}\quad [x_{i}]_{\lambda }=[y_{i,\lambda }, z_{i,\lambda }]\quad \bigl(i\in { \mathbf{Z}}(-m-k,-1), \lambda \in (0,1]\bigr), $$
(2.3)

and \(\{(y_{n,\lambda },z_{n,\lambda })\}^{\infty }_{n=-m-k} ( \lambda \in (0,1])\) is the unique positive solution of the following system of difference equations:

$$ y_{n,\lambda }=\max \biggl\{ C_{l,\lambda }, \frac{y_{{n-m-k},\lambda }}{z_{n-m,\lambda }}\biggr\} ,\qquad z_{n,\lambda }=\max \biggl\{ C_{r,\lambda }, \frac{z_{n-m-k,\lambda }}{y_{n-m,\lambda }}\biggr\} $$
(2.4)

with initial values \((y_{i,\lambda }, z_{i,\lambda })\ (i\in {\mathbf{Z}}(-m-k,-1))\). Since \(C, x_{i}\in {\mathcal{F}}^{+}\ (i\in {\mathbf{Z}}(-m-k,-1))\), there exist \(0\leq P_{0}\leq Q_{0}\) such that, for any \(\lambda _{1},\lambda _{2}\in (0,1]\) with \(\lambda _{1}\leq \lambda _{2}\), we have

$$\begin{aligned} &P_{0} \leq C_{l,\lambda _{1}}\leq C_{l,\lambda _{2}}\leq C_{r, \lambda _{2}}\leq C_{r,\lambda _{1}}\leq Q_{0}, \\ &P_{0} \leq y_{i,\lambda _{1}}\leq y_{i,\lambda _{2}}\leq z_{i, \lambda _{2}}\leq z_{i,\lambda _{1}}\leq Q_{0}\quad \bigl(i\in { \mathbf{Z}}(-m-k,-1)\bigr). \end{aligned}$$

It follows from (2.4) that, for any \(\lambda _{1},\lambda _{2}\in (0,1]\) with \(\lambda _{1}\leq \lambda _{2}\), we have

$$\begin{aligned} 0< P_{1}&=\max \biggl\{ P_{0},\frac{P_{0}}{Q_{0}}\biggr\} \\ &\leq y_{0,\lambda _{1}}=\max \biggl\{ C_{l,\lambda _{1}}, \frac{y_{{-m-k},\lambda _{1}}}{z_{-m,\lambda _{1}}}\biggr\} \\ &\leq y_{0,\lambda _{2}}=\max \biggl\{ C_{l,\lambda _{2}}, \frac{y_{{-m-k},\lambda _{2}}}{_{n-m,\lambda _{2}}}\biggr\} \\ &\leq z_{0,\lambda _{2}}=\max \biggl\{ C_{r,\lambda _{2}}, \frac{z_{{-m-k},\lambda _{2}}}{y_{-m,\lambda _{2}}}\biggr\} \\ &\leq z_{0,\lambda _{1}}=\max \biggl\{ C_{r,\lambda _{1}}, \frac{z_{{-m-k},\lambda _{1}}}{y_{-m,\lambda _{1}}}\biggr\} \\ &\leq \max \biggl\{ Q_{0},\frac{Q_{0}}{P_{0}}\biggr\} =Q_{1}. \end{aligned}$$

It is easy to see that \(y_{0,\lambda }, z_{0,\lambda }\) are left continuous on \(\lambda \in (0,1]\) (see [40]) and \(\overline{\bigcup_{\lambda \in (0,1]}[y_{0,\lambda }, z_{0,\lambda }]} \subset [P_{1},Q_{1}]\) (i.e., \(\overline{\bigcup_{\lambda \in (0,1]}[y_{0,\lambda }, z_{0,\lambda }]}\) is compact). Hence \([y_{0,\lambda }, z_{0,\lambda }]\) determines a unique \(x_{0}\in \mathcal{F}^{+}\) such that \([x_{0}]_{\lambda }= [y_{0,\lambda }, z_{0,\lambda }]\) for all \(\lambda \in (0,1]\) (see [40]).

Moreover, by mathematical induction on n, it is easy to show that: (1) \(0 < y_{n,\lambda _{1}}\leq y_{n,\lambda _{2}}\leq z_{n,\lambda _{2}} \leq z_{n,\lambda _{1}}\ (n\in {\mathbf{N}}_{0})\); (2) \(y_{n,\lambda }, z_{n,\lambda }\) are left continuous for all \(n\in {\mathbf{N}}_{0}\) and \(\lambda \in (0,1]\); (3) For any \(n\in {\mathbf{N}}_{0}\), there exist \(0< P_{n+1}\leq Q_{n+1}<+\infty \) such that \(\overline{\bigcup_{\lambda \in (0,1]}[y_{n,\lambda }, z_{n,\lambda }]} \subset [P_{n+1},Q_{n+1}]\) (i.e., \(\overline{\bigcup_{\lambda \in (0,1]}[y_{n,\lambda }, z_{n,\lambda }]}\) is compact). Hence by [40], Theorem 2.1, we see that \([y_{n,\lambda }, z_{n,\lambda }]\) determines a sequence \(\{x_{n}\}_{n=-m-k}^{\infty }\) of positive fuzzy numbers such that \([x_{n}]_{\lambda }= [y_{n,\lambda }, z_{n,\lambda }]\) for every \(n\in {\mathbf{N}}_{0}\) and \(\lambda \in (0,1]\), and by Proposition 2.1 we see that \(\{x_{n}\}_{n=-m-k}^{\infty }\) is the unique positive solution of (1.1) with initial values \(x_{i}\ (i\in {\mathbf{Z}}(-m-k,-1))\). The proof is complete. □

Main results

In the sequel, let \(\{x_{n}\}_{n=-m-k}^{\infty }\) be a positive solution of (1.1) with initial values \(x_{i}\in {\mathcal{F}}^{+}\ (i\in {\mathbf{Z}}(-m-k,-1))\). Let \(\operatorname{supp} C=[C_{1},C_{2}]\). For any \(\lambda \in (0,1]\), write

$$ C_{\lambda }=[C_{l,\lambda },C_{r,\lambda }],\qquad [x_{n}]_{\lambda }=[y_{n, \lambda },z_{n,\lambda }]. $$

Then it follows from Proposition 2.2 that \(\{(y_{n,\lambda },z_{n,\lambda })\}_{n=-m-k}^{\infty }(\lambda \in (0,1])\) satisfies the following system:

$$ y_{n,\lambda }=\max \biggl\{ C_{l,\lambda }, \frac{y_{{n-m-k},\lambda }}{z_{n-m,\lambda }}\biggr\} ,\qquad z_{n,\lambda }=\max \biggl\{ C_{r,\lambda }, \frac{z_{n-m-k,\lambda }}{y_{n-m,\lambda }}\biggr\} , $$
(3.1)

with initial values \((y_{i,\lambda }, z_{i,\lambda })\ (i\in {\mathbf{Z}}(-m-k,-1))\). From (3.1) one has, for any \(n\in {\mathbf{N}}_{0}\),

$$ y_{n,\lambda }\geq C_{l,\lambda },\qquad z_{n,\lambda }\geq C_{r, \lambda }. $$
(3.2)

Theorem 3.1

If \(C_{1}>1\), then \(x_{n}=C\) eventually.

Proof

Write \(M=\max \{\sup (\operatorname{supp} x_{j}):j\in {\mathbf{Z}}(0,m+k-1) \}\). From (3.1), (3.2) and a simple inductive argument we obtain the result that, for any \(i\in {\mathbf{Z}}(0,m+k-1)\) and \(n\in {\mathbf{N}}\),

$$\begin{aligned} C_{l,\lambda }\leq y_{n(m+k)+i,\lambda }&=\max \biggl\{ C_{l,\lambda }, \frac{y_{{(n-1)(m+k)+i},\lambda }}{z_{n(m+k)+i-m,\lambda }}\biggr\} \leq \max \biggl\{ C_{l,\lambda },\frac{y_{{(n-1)(m+k)+i},\lambda }}{C_{r,\lambda }} \biggr\} \\ &\leq \max \biggl\{ C_{l,\lambda },\frac{y_{{(n-1)(m+k)+i},\lambda }}{C_{1}} \biggr\} \leq \cdots \leq \max \biggl\{ C_{l,\lambda }, \frac{y_{{i},\lambda }}{C_{1}^{n}}\biggr\} \\ &\leq \max \biggl\{ C_{l,\lambda },\frac{M}{C_{1}^{n}}\biggr\} \end{aligned}$$

and

$$\begin{aligned} C_{r,\lambda }\leq z_{n(m+k)+i,\lambda }&=\max \biggl\{ C_{r,\lambda }, \frac{z_{{(n-1)(m+k)+i},\lambda }}{y_{n(m+k)+i-m,\lambda }}\biggr\} \leq \max \biggl\{ C_{r,\lambda },\frac{z_{{(n-1)(m+k)+i},\lambda }}{C_{l,\lambda }} \biggr\} \\ &\leq \max \biggl\{ C_{r,\lambda },\frac{z_{{(n-1)(m+k)+i},\lambda }}{C_{1}} \biggr\} \leq \cdots \leq \max \biggl\{ C_{r,\lambda }, \frac{z_{{i},\lambda }}{C_{1}^{n}}\biggr\} \\ &\leq \max \biggl\{ C_{r,\lambda },\frac{M}{C_{1}^{n}}\biggr\} . \end{aligned}$$

Then there exists an \(N\in {\mathbf{N}}\) such that \(M/{C_{1}^{n}}<1\) for any \(n\geq N\), which implies \(y_{n(m+k)+i,\lambda }=C_{l,\lambda }\) and \(z_{n(m+k)+i,\lambda }=C_{r,\lambda }\) for any \(n\geq N\) and \(\lambda \in (0,1]\) and \(i\in {\mathbf{Z}}(0,m+k-1)\). Then \(x_{n}=C\) eventually. The proof is complete. □

Theorem 3.2

There exists an \(C\in {\mathcal{F}}^{+}\) with \(C_{1}=1\) such that (1.1) has a positive solution which is not eventually periodic.

Proof

Define \(C\in {\mathcal{F}}^{+}\) by

$$ C(t)= \textstyle\begin{cases} 0, & t< 1, \\ 2t-2, & 1\leq t\leq \frac{3}{2}, \\ 4-2t, & \frac{3}{2}\leq t\leq 2, \\ 0, & t>2.\end{cases} $$
(3.3)

Define \(x_{i}\in \mathcal{F}^{+}\ (i\in {\mathbf{Z}}(-m-k,-1))\) by

$$ x_{i}(t)= \textstyle\begin{cases} 0, & t< 1, \\ 2t-2, & 1\leq t\leq \frac{3}{2}, \\ 1, & \frac{3}{2}\leq t\leq 2e, \\ 0, & t>2e.\end{cases} $$
(3.4)

Then, for any \(n\in {\mathbf{N}}\),

$$ C_{\frac{1}{n}}=\biggl[1+\frac{1}{2n},2-\frac{1}{2n}\biggr],\qquad [x_{i}]_{ \frac{1}{n}}=[y_{i,\frac{1}{n}},z_{i,\frac{1}{n}}]=\biggl[1+ \frac{1}{2n},2e\biggr]\quad \bigl(i\in {\mathbf{Z}}(-m-k,-1)\bigr). $$

Write \(r=s(m+k)+i,s\in {\mathbf{N}}_{0}\ (i\in {\mathbf{Z}}(0,m+k-1))\). Note \(z_{j(m+k)+i-m,\frac{1}{n}}\geq 1\) for any \(0\leq j\leq s\). Then from (3.1) and a simple inductive argument we have

$$ \textstyle\begin{cases} 1+\frac{1}{2n}\leq y_{r,\frac{1}{n}}=\max \{1+\frac{1}{2n}, \frac{y_{{i-m-k},\frac{1}{n}}}{\prod^{s}_{j=0}z_{j(m+k)+i-m,\frac{1}{n}}} \}=1+\frac{1}{2n}, \\ 2-\frac{1}{2n}\leq z_{r,\frac{1}{n}}=\max \{2-\frac{1}{2n}, \frac{z_{{i-m-k},\frac{1}{n}}}{\prod^{s}_{j=0}y_{j(m+k)+i-m,\frac{1}{n}}} \}= \max \{2-\frac{1}{2n},\frac{2e}{(1+\frac{1}{2n})^{s+1}}\}.\end{cases} $$
(3.5)

Thus \(z_{n,\frac{1}{n}}=2e/{(1+\frac{1}{2n})^{s_{1}+1}}\) since \((2-1/2n)(1+\frac{1}{2n})^{s_{1}+1}<(2-1/2n)(1+\frac{1}{2n})^{2n}<2e\), where \(n=s_{1}(m+k)+i\). On the other hand, for any \(n\in {\mathbf{N}}\), there exists an \(N_{1}(n)\in {\mathbf{N}}\) such that \(z_{r,\frac{1}{n}}=2-\frac{1}{2n}\) for every \(r\geq N_{1}(n)\) since \(\lim_{s\longrightarrow \infty }2e/{(1+\frac{1}{2n})^{s}}=0\). Thus \([x_{r}]_{\frac{1}{n}}\neq [x_{n}]_{\frac{1}{n}}\) for any \(r>N_{1}(n)\), which implies \(\{x_{n}\}_{n=-m-k}^{\infty }\) is not eventually periodic. The proof is complete. □

Theorem 3.3

If \(C_{2}\leq 1\), then there exists a positive solution \(\{x_{n}\}_{n=-m-k}^{\infty }\) of (1.1) such that every \(x_{n}>1\) is a trivial fuzzy number (\(n\geq -m-k\)) and \(\lim_{n\longrightarrow \infty }x_{n}=1\).

Proof

We show that the following equation:

$$ w_{n}=\frac{w_{n-m-k}}{w_{n-m}},\quad n\in {\mathbf{N}}_{0} $$
(3.6)

has a decreasing solution which tends to 1. Indeed, we write

$$ M_{1}=\bigl\{ (u_{1},\ldots ,u_{m+k}):u_{m+k}u_{k+1} \geq u_{1}\geq \cdots \geq u_{m+k}\geq 1\bigr\} $$

and

$$ M_{2}=\bigl\{ (u_{1},\ldots ,u_{m+k}): u_{m+k}u_{k}\geq u_{1}\geq \cdots \geq u_{m+k}\geq 1\bigr\} . $$

Then \(M_{1}\subset M_{2}\) since for any \((u_{1},\ldots ,u_{m+k})\in M_{1}\), we have \(u_{m+k}u_{k+1}\geq u_{1}\geq \cdots \geq u_{m+k}\geq 1\) and \(u_{m+k}u_{k}\geq u_{m+k}u_{k+1}\geq x_{1}\). Now we define \(T:M_{1}\rightarrow M_{2}\), for any \((u_{1},\ldots ,u_{m+k})\in M_{1}\), by

$$ T(u_{1},\ldots ,u_{m+k})=(v_{1},\ldots ,v_{m+k})\equiv \biggl(u_{2},\ldots ,u_{m+k}, \frac{u_{1}}{u_{k+1}}\biggr). $$
(3.7)

We show that T is well defined. Indeed, it follows from (3.7) and the definition of \(M_{1}\) that

$$ \textstyle\begin{cases} v_{i}=u_{i+1}, \quad\text{for } i\in {\mathbf{Z}}\ (1,\ldots ,m+k-1), \\ v_{m+k}=\frac{u_{1}}{u_{k+1}},\end{cases} $$
(3.8)

and

$$ v_{m+k}v_{k}=\frac{u_{1}}{u_{k+1}}u_{k+1}=u_{1} \geq u_{2}=v_{1}\geq \cdots \geq v_{m+k-1}=u_{m+k} \geq \frac{u_{1}}{u_{k+1}}=v_{m+k}\geq 1. $$

Thus \((v_{1},\ldots ,v_{m+k})\in M_{2}\).

Now we show that T is a bijection from \(M_{1}\) to \(M_{2}\). Indeed, let \(u=(u_{1},\ldots ,u_{m+k}),v=(v_{1},\ldots ,v_{m+k})\in M_{1}\) with \(u\neq v\). Then \(T(u)\neq T(v)\). On the other hand, for any \(v=(v_{1},\ldots ,v_{m+k})\in M_{2}\), we have

$$ v_{m+k}v_{k}\geq v_{1}\geq \cdots \geq v_{m+k}\geq 1. $$
(3.9)

Write

$$ u=(u_{1},\ldots ,u_{m+k})\equiv (v_{m+k}v_{k},v_{1}, \ldots ,v_{m+k-1}). $$
(3.10)

By (3.9) and (3.10) we have

$$\begin{aligned} u_{m+k}u_{k+1}=v_{m+k-1}v_{k}\geq v_{m+k}v_{k}=u_{1}\geq v_{1}=u_{2} \geq \cdots \geq u_{m+k}=v_{m+k-1}\geq 1, \end{aligned}$$

which implies \(u\in M_{1}\) and by (3.7) we have \(T(u)=v\).

Furthermore, since \(T^{-1}(v_{1},\ldots ,v_{m+k})=(v_{m+k}v_{k},v_{1},\ldots ,v_{m+k-1})\) is continuous, T is a homeomorphism.

Noting that \(M_{1}\subset M_{2}\) and T is a homeomorphism from \(M_{1}\) onto \(M_{2}\), we see \(T^{-1}(M_{1})\subset T^{-1}(M_{2})=M_{1}\). By induction, it follows that, for every \(n\in {\mathbf{N}}\),

$$ p=(1,1 ,\ldots ,1)\in T^{-n}(M_{1})\subset T^{-n+1}(M_{1}). $$

Because \(M_{1}\) is a unbounded connected closed set, we see that \(T^{-n}(M_{1})\) is a unbounded connected closed set for every \(n\in {\mathbf{N}}\). Write

$$ Q=\bigcap_{n=0}^{\infty }T^{-n}(M_{1}). $$

Then Q is also a unbounded connected set.

Let \(\{w_{n}\}_{n=-k-m}^{\infty }\) be a solution of (3.6) with the initial values \((w_{-m-k},\ldots ,w_{-1})\in Q-\{p\}\). Then, for every \(n\in {\mathbf{N}}\),

$$ T^{n}(w_{-k-m},\ldots ,w_{-1})=(w_{n-k-m}, \ldots ,w_{n-1})\in M_{1}- \{p\}, $$

which implies \(w_{n}\geq w_{n+1}>1\) for any \(n\geq -k-m\). Let \(\lim_{n\longrightarrow \infty }w_{n}=a\). Then by (3.6) we have \(a=1\). It is easy to show that \(\{(w_{n},w_{n})\}_{n=-k-m}^{\infty }\) is also a solution of (3.1) which is not eventually periodic. Thus \(x_{n}=w_{n}\) is a solution of (1.1) such that every \(x_{n}>1\) (\(n \geq -m-k\)) is a trivial fuzzy number and \(\lim_{n\longrightarrow \infty }x_{n}=1\). The proof is complete. □

Theorem 3.4

If \(C_{1}<1<C_{2}\), then every positive solution \(\{x_{n}\}_{n=-m-k}^{\infty }\) of (1.1) is not eventually periodic.

Proof

Since \(C_{1}<1<C_{2}\), we see \(C_{l,\lambda _{1}}< 1<C_{r,\lambda _{1}}\) for some \(\lambda _{1}\in (0,1]\). For any \(\lambda \in (0,\lambda _{1}]\), we have

$$ 0< C_{l,\lambda }\leq C_{l,\lambda _{1}}< 1< C_{r,\lambda _{1}}\leq C_{r, \lambda }. $$

Write \(M=\max \{\sup (\operatorname{supp} x_{j}):j\in {\mathbf{Z}}(0,m+k-1) \}\). From (3.1), (3.2) and a simple inductive argument we obtain, for any \(i\in {\mathbf{Z}}(0,m+k-1)\) and \(s\in {\mathbf{N}}_{0}\) and \(\lambda \in (0,\lambda _{1}]\),

$$\begin{aligned} C_{l,\lambda }\leq y_{s(m+k)+i,\lambda }&=\max \biggl\{ C_{l,\lambda }, \frac{y_{{(s-1)(m+k)+i},\lambda }}{z_{s(m+k)+i-m,\lambda }}\biggr\} \leq \max \biggl\{ C_{l,\lambda },\frac{y_{{(s-1)(m+k)+i},\lambda }}{C_{r,\lambda }} \biggr\} \\ &\leq \max \biggl\{ C_{l,\lambda }, \frac{y_{{(s-1)(m+k)+i},\lambda }}{C_{r,\lambda _{1}}}\biggr\} \leq \cdots \leq \max \biggl\{ C_{l,\lambda }, \frac{y_{{i},\lambda }}{C_{r,\lambda _{1}}^{s}}\biggr\} \\ &\leq \max \biggl\{ C_{l,\lambda },\frac{M}{C_{r,\lambda _{1}}^{s}}\biggr\} . \end{aligned}$$

Thus there exists an \(N\in {\mathbf{N}}\) such that \(y_{n,\lambda }=C_{l,\lambda }\) for any \(n\geq N\) and \(\lambda \in (0,\lambda _{1}]\) since \(\lim_{s\longrightarrow \infty }{M}/{C_{r,\lambda _{1}}^{s}}=0\).

By (3.1) and (3.2) we see that, for any \(n\geq m+N\) and \(\lambda \in (0,\lambda _{1}]\),

$$ z_{n,\lambda }=\max \biggl\{ C_{r,\lambda }, \frac{z_{n-m-k,\lambda }}{C_{l,\lambda }}\biggr\} . $$
(3.11)

If \(z_{n,\lambda }= C_{r,\lambda }>{z_{n-m-k,\lambda }}/{C_{l,\lambda }}\) for some \(n\in {\mathbf{Z}}(m+N,m+N+m+k-1)\), then by (3.11) we obtain \(z_{n+s(m+k),\lambda }=C_{r,\lambda }/C_{l,\lambda }^{s}\) for any \(s\in {\mathbf{N}}_{0}\). If \(z_{n,\lambda }= {z_{n-m-k,\lambda }}/{C_{l,\lambda }}\geq C_{r,\lambda }\) for some \(n\in {\mathbf{Z}}\ (m+N,m+N+m+k-1)\), then by (3.11) we obtain \(z_{n+s(m+k),\lambda }=z_{n-m-k,\lambda }/C_{l,\lambda }^{s+1}\) for any \(s\in {\mathbf{N}}_{0}\). Thus \(\lim_{n\longrightarrow \infty }z_{n,\lambda }=+\infty \). Furthermore, we see that \(\{x_{n}\}_{n=-m-k}^{\infty }\) is not eventually periodic. The proof is complete. □

Availability of data and materials

None.

References

  1. 1.

    Benest, D., Froeschlè, C. (eds.): Analysis and Modelling of Discrete Dynamical Systems. Advances in Discrete Mathematics and Applications., vol. 1. Gordon & Breach, Amsterdam (1998)

    Google Scholar 

  2. 2.

    Edelstein-Keshet, L.: Mathematical Models in Biology. The Random House/Birkhauser Mathematics Series. Random House, New York (1988)

    Google Scholar 

  3. 3.

    Popov, E.P.: Automatic Regulation and Control. Nauka, Moscow (1966)

    Google Scholar 

  4. 4.

    Gao, Y., Zhang, G.: Oscillation of nonlinear first order neutral difference equations. Appl. Math. E-Notes 1, 5–10 (2001)

    MathSciNet  MATH  Google Scholar 

  5. 5.

    Berenhaut, K.S., Foley, J.D., Stević, S.: Boundedness character of positive solutions of a max difference equation. J. Differ. Equ. Appl. 12, 1193–1199 (2006)

    MathSciNet  Article  Google Scholar 

  6. 6.

    Sauer, T.: Global convergence of max-type equations. J. Differ. Equ. Appl. 17, 1–8 (2011)

    MathSciNet  Article  Google Scholar 

  7. 7.

    Shi, Q., Su, X., Yuan, G.: Characters of the solutions to a generalized nonlinear max-type difference equation. Chin. Ann. Math., Ser. B 28, 284–289 (2013)

    MATH  Google Scholar 

  8. 8.

    Stević, S.: Representation of solutions of bilinear difference equations in terms of generalized Fibonacci sequences. Electron. J. Qual. Theory Differ. Equ. 67, 1 (2014)

    MathSciNet  MATH  Google Scholar 

  9. 9.

    Stević, S., Alghamdi, M.A., Alotaibi, A., Shahzad, N.: Boundedness character of a max-type system of difference equations of second order. Electron. J. Qual. Theory Differ. Equ. 45, 1 (2014)

    MathSciNet  MATH  Google Scholar 

  10. 10.

    Stević, S., Alghamdi, M.A., Alotaibi, A., Shahzad, N.: Eventual periodicity of some systems of max-type difference equations. Appl. Math. Comput. 236, 635–641 (2014)

    MathSciNet  MATH  Google Scholar 

  11. 11.

    Stević, S., Iričanin, B.D., Smarda, Z.: On a product-type system of difference equations of second order solvable in closed form. J. Inequal. Appl. 2015, 327 (2015)

    MathSciNet  Article  Google Scholar 

  12. 12.

    Sun, T., Xi, H.: On the solutions of a system of difference equations with maximum. Appl. Math. Comput. 290, 292–297 (2016)

    MathSciNet  MATH  Google Scholar 

  13. 13.

    Sun, T., He, Q., Wu, X., Xi, H.: Global behavior of the max-type difference equation \(x_{n} =\max\{{1}/ {x_{n-m}},{A_{n}}/ {x_{n-r}}\}\). Appl. Math. Comput. 248, 687–692 (2014)

    MathSciNet  Google Scholar 

  14. 14.

    Xiao, Q., Shi, Q.: Eventually periodic solutions of a max-type equation. Math. Comput. Model. 57, 992–996 (2013)

    MathSciNet  Article  Google Scholar 

  15. 15.

    Yazlik, Y., Tollu, D.T., Taskara, N.: On the solutions of a max-type difference equation system. Math. Methods Appl. Sci. 38, 4388–4410 (2015)

    MathSciNet  Article  Google Scholar 

  16. 16.

    Mishev, D., Patula, W.T., Voulov, H.D.: A reciprocal difference equation with maximum. Comput. Math. Appl. 43, 1021–1026 (2002)

    MathSciNet  Article  Google Scholar 

  17. 17.

    Fotiades, E., Papaschinopoulos, G.: On a system of difference equations with maximum. Appl. Math. Comput. 221, 684–690 (2013)

    MathSciNet  MATH  Google Scholar 

  18. 18.

    Su, G., Sun, T., Qin, B.: On the solutions of a max-type system of difference equations with period-two parameters. Adv. Differ. Equ. 2018, 358 (2018)

    MathSciNet  Article  Google Scholar 

  19. 19.

    Hatir, E., Mansour, T., Yalcinkaya, I.: On a fuzzy difference equation. Util. Math. 93, 135–151 (2014)

    MathSciNet  MATH  Google Scholar 

  20. 20.

    He, Q., Tao, C., Sun, T., Liu, X., Su, D.: Periodicity of the positive solutions of a fuzzy max-difference equation. Abstr. Appl. Anal. 2014, Article ID 760247 (2014)

    MathSciNet  MATH  Google Scholar 

  21. 21.

    Horcik, R.: Solution of a system of linear equations with fuzzy numbers. Fuzzy Sets Syst. 159, 1788–1810 (2008)

    MathSciNet  Article  Google Scholar 

  22. 22.

    Lakshmikantham, V., Vatsala, A.S.: Basic theory of fuzzy difference equations. J. Differ. Equ. Appl. 8, 957–968 (2002)

    MathSciNet  Article  Google Scholar 

  23. 23.

    Nguyen, H.T., Walker, E.A.: A First Course in Fuzzy Logic. CRC Press, Florida (1997)

    Google Scholar 

  24. 24.

    Papaschinopoulos, G., Papadopoulos, B.K.: On the fuzzy difference equation \(x_{n+1} = A+ {B}/{x_{n}}\). Soft Comput. 6, 456–461 (2002)

    Article  Google Scholar 

  25. 25.

    Stefanidou, G., Papaschinopoulos, G.: A fuzzy difference equation of a rational form. J. Nonlinear Math. Phys. 12, 300–315 (2005)

    MathSciNet  Article  Google Scholar 

  26. 26.

    Stefanidou, G., Papaschinopoulos, G., Schinas, C.J.: On an exponential-type fuzzy difference equation. Adv. Differ. Equ. 2010, Article ID 196920 (2010)

    MathSciNet  Article  Google Scholar 

  27. 27.

    Zhang, Q., Liu, J.: On first order fuzzy difference equation \(x_{n+1}=Ax_{n}+B\) (in Chinese). Fuzzy Syst. Math. 23, 74–79 (2009)

    Google Scholar 

  28. 28.

    Zhang, Q., Liu, J., Luo, Z.: Dynamical behavior of a third-order rational fuzzy difference equation. Adv. Differ. Equ. 2015, Article ID 513662 (2015)

    MathSciNet  Google Scholar 

  29. 29.

    Zhang, Q., Yang, L., Liao, D.: On the fuzzy difference equation \(x_{n+1}=A+\sum^{k}_{i=0}B/x_{n-i}\). World Acad. Sci., Eng. Technol. 75, 1032–1037 (2011)

    Google Scholar 

  30. 30.

    Zhang, Q., Yang, L., Liao, D.: Behavior of solutions to a fuzzy nonlinear difference equation. Iran. J. Fuzzy Syst. 9, 1–12 (2012)

    MathSciNet  MATH  Google Scholar 

  31. 31.

    Zhang, Q., Yang, L., Liao, D.: On first order fuzzy Ricatti difference equation. Inf. Sci. 270, 226–236 (2014)

    MathSciNet  Article  Google Scholar 

  32. 32.

    Chrysafis, K.A., Papadopoulos, B.K., Papaschinopoulos, G.: On the fuzzy difference equations of finance. Fuzzy Sets Syst. 159, 3259–3270 (2008)

    MathSciNet  Article  Google Scholar 

  33. 33.

    Deeba, E.Y., De Korvin, A.: Analysis by fuzzy difference equations of a model of \(CO_{2}\) level in the blood. Appl. Math. Lett. 12, 33–40 (1999)

    MathSciNet  Article  Google Scholar 

  34. 34.

    Ur Rahman, G., Din, Q., Faizullah, F., Khan, F.M.: Qualitative behavior of a second-order fuzzy difference equation. J. Intell. Fuzzy Syst. 34, 745–753 (2018)

    Article  Google Scholar 

  35. 35.

    Stefanidou, G., Papaschinopoulos, G.: Behavior of the positive solutions of fuzzy max-difference equations. Adv. Differ. Equ. 2, 153–172 (2005)

    MathSciNet  MATH  Google Scholar 

  36. 36.

    Stefanidou, G., Papaschinopoulos, G.: The periodic nature of the positive solutions of a nonlinear fuzzy max-difference equation. Inf. Sci. 176, 3694–3710 (2006)

    MathSciNet  Article  Google Scholar 

  37. 37.

    Sun, T., Xi, H., Su, G., Qin, B.: Dynamics of the fuzzy difference equation \(z_{n} = \max \{{1}/{z_{n-m}}, {\alpha _{n}}/{z_{n-r}}\}\). J. Nonlinear Sci. Appl. 11, 477–485 (2018)

    MathSciNet  Article  Google Scholar 

  38. 38.

    Papaschinopoulos, G., Papadopoulos, B.K.: On the fuzzy difference equation \(x_{n+1} = A + {x_{n}}/{x_{n-m}}\). Fuzzy Sets Syst. 129, 73–81 (2002)

    Article  Google Scholar 

  39. 39.

    Papaschinopoulos, G., Stefanidou, G.: Boundedness and asymptotic behavior of the solutions of a fuzzy difference equation. Fuzzy Sets Syst. 140, 523–539 (2003)

    MathSciNet  Article  Google Scholar 

  40. 40.

    Wu, C., Zhang, B.: Embedding problem of noncompact fuzzy number space \(E^{-} \)(I). Fuzzy Sets Syst. 105, 165–169 (1999)

    MathSciNet  Article  Google Scholar 

Download references

Acknowledgements

The authors would like to thank the referees for their valuable comments and suggestions.

Funding

The research was supported by NNSF of China (11761011, 71862003) and SF of Guangxi University of Finance and Economics (2019QNB10).

Author information

Affiliations

Authors

Contributions

All authors participated in every phase of research conducted for this paper. All authors read and approved the final manuscript.

Corresponding author

Correspondence to Guangwang Su.

Ethics declarations

Competing interests

The authors declare that they have no competing interests.

Rights and permissions

Open Access This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http://creativecommons.org/licenses/by/4.0/.

Reprints and Permissions

About this article

Verify currency and authenticity via CrossMark

Cite this article

Han, C., Su, G., Li, L. et al. Eventual periodicity of the fuzzy max-difference equation \(x_{n} = \max \{ C, \frac{x_{n-m-k}}{x_{n-m}}\}\). Adv Differ Equ 2020, 673 (2020). https://doi.org/10.1186/s13662-020-03136-4

Download citation

Keywords

  • Fuzzy max-type difference equation
  • Positive solution
  • Eventual periodicity
\